Turtle in a tree - Hudson, Neesha (New York : Dial Books for Young Readers, 2021)
Two dogs learn the importance of listening to others when they disagree over what they see in a tree.
Ages 3-7.
Grades K-1.
Keywords: Perception -- Fiction; Quarreling -- Fiction; Apologizing -- Fiction; Dogs -- Fiction; Animals -- Fiction